FISCAL AND CONTROL FUNCTION OF CUSTOMS ADMINISTRATION WITH RESPECT TO THE COLLECTION OF CUSTOMS AND TAX DUTIES - Adam Drozdek (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2015)
Customs Administration plays an important role in protecting the fiscal interests of the European Community. Customs service, as part of the Community Customs Administration is responsible for ensuring the safety and protection of fiscal interests not only of the Polish territory, but also of other Member States. Despite the abolition of customs borders between Member States, the role of the Customs service did not diminish, on the contrary, it is still growing. As a result, customs administration organs are equipped with a range of competencies associated with the collection of customs and tax duties on imported goods.